2006
DOI: 10.1002/bit.21198
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the extraction kinetics and diffusivity of Cyclosporin A in the fungus Tolypocladium inflatum

Abstract: The influence of temperature on the extraction kinetics of Cyclosporin A (CyA) from the mycelia of Tolypocladium inflatum was examined in this study. The extraction of CyA from mycelia was performed in a 2-L stirred, baffled vessel using 30% v/v aqueous methanol. The temperature range used was from 5 to 45 degrees C. A linear relationship was found between the extraction yield of CyA and temperature. As the temperature increased, the yield of CyA increased with a maximum CyA yield of 18.3% obtained at 45 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The diffusion and extraction processes of natamycin from the hypha of S. gilvosporeus into the solvent can be described well by the diffusion theory and mass extraction equilibrium theory. However, the overall mass transfer coefficient is only applicable to specific batch of extraction, and would have to be determined for different batches based on biomass type, batch size, solvent volume, and solvent type used in the extraction processes 17, 32…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The diffusion and extraction processes of natamycin from the hypha of S. gilvosporeus into the solvent can be described well by the diffusion theory and mass extraction equilibrium theory. However, the overall mass transfer coefficient is only applicable to specific batch of extraction, and would have to be determined for different batches based on biomass type, batch size, solvent volume, and solvent type used in the extraction processes 17, 32…”
Section: Resultsmentioning
confidence: 99%
“… Proposed schematic diagram of the mass transfer trajectory of natamycin from the vacuole of S. gilvosporeus to the solvent liquid phase 16, 17…”
Section: Theory and Modelingmentioning
confidence: 99%
“…In 2008, Chen reviewed the panorama of sample preparation methods and highlighted some of the most promising methods. After that, a series of review articles were reported focusing on different specific sample preparation methods such as SPME , MAE , supercritical fluid extraction (SFE) , etc. along with miniaturization and online coupling sample preparation methods .…”
Section: Introductionmentioning
confidence: 99%